2019
DOI: 10.1186/s12877-019-1162-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding carers’ fall concern and their management of fall risk among older people at home

Abstract: Background Many older people (care recipients) experience long-term psychological distress due to the fear of falling again. Falls can affect carers due to concerns about their care recipients falling. Understanding carers’ fall concern is crucial to determine if carers are coping with the provision of care or have adequate knowledge and support in preventing their care recipients from falling at home. Methods A descriptive qualitative study was conducted to explore car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Given the complexity of the post-fall time period and the SNF placement decision-making process, qualitative research is well suited to assess generated themes. Prior qualitative studies have assessed community caregivers' concerns of care recipients' risk of falling and management at home, 23 as well as families' experiences with relationships and the quality of care following SNF placement of an older relative. 24 Ang et al 23 identified four themes in their interviews with carers: carers' perception of fall and fall risk, care recipient's behavior and attitude towards fall risk, care recipient's health and function, and care recipient's living environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of the post-fall time period and the SNF placement decision-making process, qualitative research is well suited to assess generated themes. Prior qualitative studies have assessed community caregivers' concerns of care recipients' risk of falling and management at home, 23 as well as families' experiences with relationships and the quality of care following SNF placement of an older relative. 24 Ang et al 23 identified four themes in their interviews with carers: carers' perception of fall and fall risk, care recipient's behavior and attitude towards fall risk, care recipient's health and function, and care recipient's living environment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior qualitative studies have assessed community caregivers' concerns of care recipients' risk of falling and management at home, 23 as well as families' experiences with relationships and the quality of care following SNF placement of an older relative. 24 Ang et al 23 identified four themes in their interviews with carers: carers' perception of fall and fall risk, care recipient's behavior and attitude towards fall risk, care recipient's health and function, and care recipient's living environment. The findings of our study highlight the many factors in the post-fall period that patients and caregivers consider in determining if SNF placement is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…From the evidence on falls prevention, the model of potential intervention considerations we developed (Fig. 1 ) is also supported by existing quantitative and qualitative evidence [ 8 , 11 , 21 ]. Physical and functional impairments [ 22 ] and living alone are associated with ability to get up after a fall [ 23 ]; only one staff participant highlighted that time and exercise training may be required to get people to the point of having the physical ability to get up, yet the benefits of maintaining activity for older people is recognised and has similar barriers to those we identified.…”
Section: Discussionmentioning
confidence: 89%
“…It is not only the person who has fallen who suffers; carers suffer distress due to the person fallen not being able to get up, or not being able to help them. They may be unsure how best to assist, which may result in their own injury or the need for additional assistance [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent qualitative study further explored the impact of older people's fall risk on carers and their management of fall risk at home (Ang, O’Brien, & Wilson, 2019). The findings revealed that fall concern was not limited to the intrinsic factors related to the older person such as ageing, cognitive and functional decline, or non‐compliance to fall prevention advice which can increase the risk of falling.…”
Section: Introductionmentioning
confidence: 99%